Una Propuesta Didáctica Desde La Educación Matemática Crítica Para Abordar El Concepto De Área Con Estudiantes De Grado Una Propuesta Didáctica Desde La Educación Matemática Crítica Para Abordar El Concepto De Área Con Estudiantes De Grado Sexto De La Localidad De Usme - Amaya Castillo, Luisa Fernanda (Universidad Antonio Nariño, 2023)
In this degree work, it was translated into didactic guidelines that develop the concept of area in the mathematics class that develop critical thinking from critical mathematics education. The main objectives were directed to the development of characterization instruments, validation instrument and didactic material that corresponded to stage six of Skovsmose (2002), based on the real context in which students live.